A Case of an Infantile Lingual Leiomyomatous Hamartoma - Gao, Thomas Z.; Schafer, Austin; Althubaiti, Abdulrahman; Fung, Bonita; Elmaraghy, Charles (Case Reports in Otolaryngology, 2022)
Lingual leiomyomatous hamartomas are rare lesions of the tongue with largely unknown mechanisms of formation. These lesions are often asymptomatic, though they may present with symptoms, particularly relating to swallow function. Workup should include imaging of the head and neck, and diagnosis should be made histologically. Treatment is surgical excision. This case is a report of a 4-week-old female who presented for evaluation of an asymptomatic 1 × 1 cm dorsal midline tongue mass discovered at birth. The patient was monitored until the age of 9 months, at which time the mass was surgically excised. The patient had an uncomplicated postoperative course. Pathological analysis yielded a diagnosis of leiomyomatous hamartoma.